Meningkatkan Kemampuan Motorik Kasar Anak Melalui Kegiatan Lempar Bola Di Paud Tunas Bangsa Kabupaten Seluma - Ratnawati Ratnawati; Asnawati Asnawati; Ranny Fitria Imran (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The purpose of this study was to determine the improvement of children's gross motor skills through ball throwing activities at Tunas Bangsa PAUD, Seluma Regency. This study is a Classroom Action Research (CAR) or also called Classroom action research with the procedure used in the form of a cycle. The subjects of this study were 15 children in group B at Tunas Bangsa PAUD. The study was conducted in two cycles of two meetings. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis being used to determine the improvement of the process expressed in a predicate, while quantitative analysis was used to determine the improvement of results using percentages. The results of improving children's gross motor skills through ball throwing activities at Tunas Bangsa PAUD, Seluma Regency in the first cycle of the first meeting with a percentage of 39.16%, in the first cycle of the second meeting with a percentage of 48.43%, in the second cycle of the first meeting with a percentage of 64.84,31% and in the second cycle of the second meeting with a percentage of 87.91%. The conclusion of the study is that children's gross motor skills through ball throwing activities at Tunas Bangsa PAUD, Seluma Regency, were proven to have increased in cycle II, meeting II, with a percentage of achievement of 87.91% with the criteria of very good development (BSB).